ANALYSIS OF WORK ENVIRONMENT, WORK MOTIVATION AND WORKLOAD ON JOB SATISFACTION IN SENIOR HIGH SCHOOLS STABAT PREPARATION PRIVATE HIGH SCHOOL - Rizki Dwi Ananda; Hidayati Purnama Lubis; H. Akhmad Taufik (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research was conducted at the Stabat Preparatory Private High School. The analysis of this research aims to determine whether the work environment, work motivation and workload influence teacher job satisfaction. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses multiple linear regression analysis. The sample in this study was 39 respondents. Primary data collection uses a questionnaire. The research results show that the results of the hypothesis test with a t value of 3.011 > t table of 2.02 with a significant value of 0.005 < 0.05, then hypothesis H2 is accepted and H0 is rejected, meaning that work motivation has a partially positive and significant effect on job satisfaction. Hypothesis test results with a t value of 3.011 > t table of 2.02 with a significant value of 0.005 < 0.05, then hypothesis H2 is accepted and H0 is rejected, meaning that work motivation has a partially positive and significant effect on job satisfaction. Hypothesis test results with a t value of 0.242 < t table of 2.02 with a significant value of 0.810 > 0.05, then hypothesis H3 is rejected and H0 is accepted, meaning that workload has no partial significant effect on job satisfaction. Test results with a value of 47.588 which is greater than 2.87 and the significant value of 0.000 is smaller than 0.05 so it can be concluded that hypothesis 4 is accepted and hypothesis 0 is rejected so it can be concluded that the work environment, work motivation and workload have a significant effect simultaneously on job satisfaction.